The effect of fluorine-containing inhibitors of corrosion of copper in atmospheric conditions - M. G. Ivanov; A. V. Nechaev; V. S. Mokrushin; O. I. Ostroukhova (Chimica Techno Acta)
The effect of fluorine-containing inhibitors of corrosion of copper in atmospheric conditions was studied by method of removing anodic polarization curves and corrosion of full-scale tests. The introduction of the inhibiting compositions as corrosion inhibitor of copper polyfluorinated amines leads to a decrease of the peak current of active dissolution of copper, which increases the corrosion resistance of copper wire rod during transportation in various climate conditions.